STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SD NEGERI 2 KOTA BANDA ACEH - Aida Nirwana; Murniati AR; Yusrizal . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: The leadership skills of a school principal are very significant in increasing the motivation of teachers. The professional competence of teachers is one of the strategies to increase the quality of education. The purpose of this study was to determine the efforts made by principals to improve the professional competence of teachers at SDN 2 Banda Aceh. This study used a qualitative approach with descriptive methods. Data was collected through interviews, observation and documentation. Subjects were the principal, deputy principal, head of KKG and teachers at SDN 2 Banda Aceh. The results showed that: (1) the principal’s policy process to improve the competence of teachers at SDN 2 Banda Aceh can be said to be good, the principal in improving teacher competence gave permission to teachers to continue their study, conducted trainings, provided teaching materials in accordance with applicable curriculum; (2) The strategies of the principal in improving the professional competence of teachers at SDN 2 Banda Aceh were good because every teacher is obliged to make a set of learning devides according to the latest curriculum, to adjust to the teacher’s book, and to make a schedule of supervision; (3) There were constraints faced by principals in improving the professional competence of teacher at SDN 2 Banda Aceh, namely the division of duties to teachers was uneven, and teachers were reluctant to express their desire and weaknesses in learning.Keywords: Strategies of the principal and Profefessional Competence of TeacherAbstrak: Kemampuan seorang kepala sekolah dalam memimpin  berpengaruh dalam meningkatkan motivasi kerja guru. Kompetensi profesional guru merupakan  strategi  meningkatkan mutu pendidikan. Tujuan penelitian ini adalah untuk mengetahui upaya-upaya yang dilakukan kepala sekolah dalam meningkatkan kompetensi profesional guru pada SD Negeri 2 kota Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui wawancara, observasi dan studi dokumentasi. Subjek penelitian adalah Kepala Sekolah, Wakil kepala sekolah, ketua KKG dan guru di SD Negeri 2 kota Banda Aceh. Hasil penelitian menunjukkan bahwa: (1) Proses kebijakan  kepala sekolah dalam meningkatkan kompetensi guru pada SD Negeri 2 Banda Aceh sudah dikatakan baik,   kepala sekolah dalam meningkatkan kompetensi guru yaitu memberi izin kepada guru untuk melanjutkan kuliah, mengadakan pelatihan, menyediakan bahan ajar yang sesuai dengan kurikulum yang berlaku; (2)  Strategi kepala sekolah dalam meningkatkan kompetensi profesional guru pada SD Negeri 2 Banda Aceh yaitu  sudah baik karena setiap guru wajib membuat perangkap pembelajaran sesuai dengan kurikulum yang terbaru, menyesuaikan buku pengangan guru, membuat jadwal supervisi; (3) Kendala-kendala yang dihadapi kepala sekolah dalam   meningkatkan kompetensi profesional guru pada SD Negeri 2 Banda Aceh yaitu pembagian tugas kepada guru kurang merata, guru tidak berani mengemukakan keinginan serta kekurangannya dalam pembelajaran.Kata Kunci: Strategi Kepala Sekolah dan Kompetensi Profesional Guru